Social Resilience and Forest Ecology Change: A study on around forest society in Simalungun District - Siburian, Robert (Jurnal Penelitian Kesejahteraan Sosial, 2018)
People who live around and depend on forest resources are susceptible to change of forest ecology, especially on the impact of forest degradation. Forest provides environment service and irreplaceable economic resources. This is why forest ecology change brings much impact to forest function capacity which implies to the decreasing of its function capacity in providing environment service and economic resources. The life of around forest society can continue if their social resilience is able to cope with the change. This research is aimed to study forest area condition in Simalungun District and that of its society’s dependency level on forest resources. It used a qualitative approach and the technique of collecting data was conducted by using indepth interview, focus group discussion (FGD) and observation. The result of the research shows that the society involvement in managing forest resources has not been significant though the government has opened the scheme of doing so as an effort to improve the forest society welfare and to enhance their social resilience.